Bibliometric study of the production and use of the Farmacia Hospitalaria journal (2004-2012) - J. Sanz-Valero; V. Tomás-Casterá; V. Tomás-Gorriz (Farmacia Hospitalaria)
Objetive: To analyze the scientific activity and the production of information of the Farmacia Hospitalaria journal as the Spanish scientific publication of reference in the pharmaceutical area. Methods: Transversal descriptive study of the results obtained from the bibliometric analysis of the articles published in the journal. Data was obtained from direct querys and Internet access to the scientific literature contained in the electronic version of the journal during the 2004-2012 period. Results: During the period studied 756 articles were published. The number of original articles was 258 (34.12%) with a productivity index of 2.40. The number of institutions identified with published articles was 246. The predominant language was Spanish with 733 (96.96%) articles. We counted 1828 keywords, of which 527 (28.83%) coincided with MeSH. The median calculation of the obsolescence of quoted references was 10, and the Price Index was 8.81%. The percentage of selfquotes was 5.18%. Conclusions: We confirmed a low proportion of original articles and an adequate percentage of satisfactory quotable articles. The low percentage of keywords that coincide with Medical Subject Headings is noteworthy. The bibliographical references found in the articles come mainy from the English-speaking area and from journals indexed in the Journal Citation Report. The obsolescence analysis of these references produced high results.